Strengthening Discipline Character of Students at Muhammadiyah Boarding-School (MBS) Muhiba Yogyakarta - Baehaqi, M Lutfi; Murdiono, Mukhamad (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Educational issues require special attention, especially those related to character. Learning in boarding-based schools is one option to overcome character problems, especially disciplined characters. This research was conducted at MBS Muhiba Yogyakarta as one of the boarding-based schools in the city of Bantul, Yogyakarta. This research was a descriptive research with a qualitative approach. Data collection was obtained by observation, interviews, documentation, and questionnaires. The instruments were interview guidelines, observation guidelines, and documentation guidelines. The subjects in this study were the director and teacher. Data analysis techniques used interactive analysis which includes; data collection, data reduction, data presentation, and conclusions. The results showed that the strengthening students discipline character of learning in boarding-based schools was carried out through; use of the inquiry learning model based on contextual, Islamic habituation, one of rule, the provision of penalties and gifts, and role model. The obstacle reinforcement of strengthening discipline character of students at boarding-based school includes specific obstacles such as; difficulty in planning material concepts and difficulty in designing the flow of thought. General obstacles in learning include; the difficulty to cooperate with parents in implementing one of rule, the teacher's insistence to implement discipline, and the lack of attention given to learning.